Development of a Visual-Based Pocketbook to Prevent Bullying Among Early Childhood Learners - Karimah, Karimah; Vinayastri, Amelia; Safi'i, Imam (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
Bullying has become a common phenomenon among early childhood students, particularly in kindergarten settings. Children aged 4–6 years often experience and engage in verbal, social, and physical bullying. This study aims to develop a pocketbook as an educational tool for teachers and parents, providing information on bullying prevention strategies for young children. The pocketbook incorporates visual illustrations to enhance understanding and was implemented in three early childhood education institutions. The research follows the Research and Development (R&D) approach using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. The study involved an initial needs analysis, revealing that parents and teachers have limited awareness of bullying. Data collection was conducted through interviews with teachers and parents, observations, content validation, language evaluation, and media validation to assess the feasibility of the pocketbook before implementation. Data analysis was performed using Aiken’s index to determine the effectiveness of the pocketbook in preventing bullying. The findings indicate that the pocketbook is an effective method for raising awareness and preventing bullying in early childhood. This is supported by data analysis, showing that the highest response rating from teachers and parents was on a 7-point scale, with an average approval rate of 49%, demonstrating a positive reception. The pocketbook serves as an innovative educational tool, enriching teachers’ and parents’ knowledge in guiding children to avoid bullying behaviors. Future research should focus on providing training sessions for teachers and parents to optimize the use of the pocketbook, ensuring more effective communication and comprehension of its content.